Geographical Variation in Preschoolers’ Screen Time: Parenting, Sibling, and Peer Relationships - Vivi Irzalinda; Melly Latifah; Dwi Hastuti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: In the digital age, excessive screen time has become a significant concern for preschool children, affecting their social, emotional, and behavioral development. This study examined the influence of parenting patterns, sibling relationships, and peer interactions on screen time, considering differences in geographical contexts. Methods: A cross-sectional quantitative design with cluster random sampling was conducted in Bandar Lampung City, Indonesia, covering mountainous (Kemiling) and coastal (Teluk Betung Timur and Bumi Waras) subdistricts. The sample included 301 families with children aged 4–7 years, living with both parents and having siblings. Data were analyzed using independent t-tests to compare differences between groups. Results: Results indicated that disciplinary parenting patterns were more effective in coastal areas, while play-based parenting patterns were stronger in mountainous areas. Sibling interaction and acceptance were higher in mountainous regions, whereas sibling rivalry was greater in coastal areas. No significant differences were found in peer interactions between the two regions. Children in coastal areas exhibited higher screen time than those in mountainous areas. Conclusion: These findings highlight the importance of geographical context in shaping children’s screen-related behaviors and family dynamics. The study emphasizes the need for geographically tailored interventions, including culturally adapted parental guidance in coastal and mountainous areas, sibling-based alternatives to screen use in mountainous areas, and integration of caregiver training with equitable internet access policies within early childhood education frameworks. Public health campaigns should integrate the WHO and American Academy of Pediatrics-recommended screen time guidelines (<1 hour/day) while promoting non-digital activities, particularly in coastal populations with higher device exposure.